Prekmurje leta 1917 - Kerec, Darja (Studia Historica Slovenica, 2018)
In this paper the publishing of Klekl in the penultimate year of the First World War is presented. The population in Prekmurje got most of its news from the frontlines from the local newspaper Novine, which was published and edited by priest Jožef Klekl. Most of the content is related to the conditions at home (Prekmurje) and more broadly (Austria-Hungary). News deemed of special importance was news in the crime section (general shortage, theft, smuggling) and news of missing or dead compatriots. In this section Klekl also used his editorial right to point out and warn about false local "news", and publish denials. Entertaining and worrisome local and foreign news are also not lacking. Amongst the latter especially reports on events in Russia, South America, the United States and Palestine, stand out.
Keywords: časopisje; informiranje; Prekmurje; prva svetovna vojna; Slovenija; svetovna vojna 1914-1918; zgodovina